The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1128/aac.02176-18
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymyxin Combination with the Antiretroviral Zidovudine Exerts Synergistic Killing against NDM-Producing Multidrug-Resistant Klebsiella pneumoniae

Abstract: Polymyxins are used as a last-line therapy against multidrug-resistant (MDR) New Delhi metallo-β-lactamase (NDM)-producingKlebsiella pneumoniae. However, polymyxin resistance can emerge with monotherapy; therefore, novel strategies are urgently needed to minimize the resistance and maintain their clinical utility. This study aimed to investigate the pharmacodynamics of polymyxin B in combination with the antiretroviral drug zidovudine againstK. pneumoniae. Three isolates were evaluated in static time-kill stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
5
18
0
Order By: Relevance
“…We demonstrated the evident synergy between AZT and colistin using the checkerboard method ( Table 4 ) and nematode killing assay ( Table 5 ). The synergistic activity of polymyxins and AZT among E. coli and K. pneumoniae carrying various resistance mechanisms ( Table 6 ) has been reported in several previous studies [ 32 , 33 , 34 , 35 ]. The most commonly investigated resistance genotypes are mcr1 and bla NDM-1 .…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…We demonstrated the evident synergy between AZT and colistin using the checkerboard method ( Table 4 ) and nematode killing assay ( Table 5 ). The synergistic activity of polymyxins and AZT among E. coli and K. pneumoniae carrying various resistance mechanisms ( Table 6 ) has been reported in several previous studies [ 32 , 33 , 34 , 35 ]. The most commonly investigated resistance genotypes are mcr1 and bla NDM-1 .…”
Section: Discussionsupporting
confidence: 58%
“…Given that colistin lyses GNB by permeabilizing the outer membrane, it is hypothesized that this mechanism allows AZT to enter the cell at increased intracellular drug concentrations [ 38 ]. Lin et al demonstrated that higher polymyxin B concentrations could increase outer membrane permeability, with simultaneous decreases in AZT MIC [ 33 ]. In addition, AZT can synergize with colistin by exerting a shared outer membrane disrupting effect [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, AZT-resistant E. coli and Salmonella were recovered from patients receiving AZT treatment for HIV infection (89,90). Recently, and in light of growing AMR, the antimicrobial properties of AZT have been explored (68)(69)(70)(71)73).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the combination of chlorpromazine with the antifungal amphotericin B was synergistic against Cryptococcus neoformans [32] . Our laboratory previously demonstrated that the antibacterial effect of polymyxin B is synergistic in combination with non-antibiotic drugs such as closantel, ivacaftor, tamoxifen, raloxifene, toremifene, mitotane, and zidovudine [27] , [28] , [29] , [30] , [33] , [34] , [35] . The focus of the present study was to evaluate the antibacterial synergy of phenothiazine neuroleptic drugs in combination with polymyxin B against a range of polymyxin resistant and susceptible Gram-negative isolates and investigate potential antimicrobial mode of action using untargeted metabolomics and scanning and transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%